Growing up in America : an atlas of youth in the USA - Sanders, Rickie; Mattson, Mark T. (Macmillan Library Reference Prentice Hall International, 1998)
This essential resource examines key issues in contemporary America from the perspective of their impact on young people. A unique visual format transforms data on such topics as health, race, immigration, crime, education, poverty and more, into an accessible portrait of the status of American youth today, and shows how that status has changed over the latter half of the 20th century.